Keeping it private: financial reporting by large proprietary companies in Australia. (28th January 2019) - Potter, Brad; Pinnuck, Matthew; Tanewski, George; Wright, Sue
Abstract: Since 2010, proprietary companies have had a choice of preparing three types of financial reports that vary in scope. We find that between 2010 and 2015, most proprietary companies in our random sample chose the lowest scope option, with very low quality financial reports. Few adopted the new option provided by AASB 1053 Application of Tiers of Australian Accounting Standards . The characteristics of the firms that adopted each type of report are consistent with the regulator's intention. Our findings should provide a better understanding of how accounting standards impact practice, and should assist regulators to reform private company financial reporting.